Nutritional Status of Child labourers in Dhaka city of Bangladesh: Findings from a Cross Sectional Study (Bangladesh Journal of Child Health, 2015)
Background: Nearly 7.9 million children are working in Bangladesh; many of which in urban areas, particularly in Dhaka city. Working during childhood impedes the childrens growth potential leading to malnutrition. The objective of this study was to investigate the nutritional status and food intake pattern of child laborers of Dhaka city, Bangladesh. Methodology: The study followed a cross-sectional study design and was conducted among 100 randomly selected child laborers (aged 5-17 years) from an NGO led school of Dhaka. Anthropometric measurements were taken using standard methods while socio-economic status and dietary intake were assessed through interviewing the respondents with a pretested questionnaire. Data were analyzed using SPSS, Epi info and MS excel DANS(R) software. Results: Forty five percent children were fixed salary earners and 89% of them worked to support their family. Anthropometric assessment reveled that, 26%, 15% and 26% respondents were stunted, wasted and underweight respectively. According to BMI for age, 39% of the children were thinner. Overall, 52.1% and 60.8% of the calorie requirement and 77.6% and 82.2% of the protein requirement were fulfilled by boys and girls respectively. Almost all the micronutrients requirement except that of thiamin and vitamin C were very poorly fulfilled. Conclusions: Overall, nutritional status of the child laborers were below acceptance. Per capita dietary intake was poor and imbalanced containing very low amount of micronutrients leading to malnutrition. Nutrition intervention program needs to be administered especially targeting working children. Adult unemployment and underemployment should be reduced and parents need to make aware of the harmful nutritional impact of working in childhood. DOI: http://dx.doi.org/10.3329/bjch.v38i3.22821 Bangladesh J Child Health 2014; VOL 38 (3) :130-136